2015
DOI: 10.1039/c5ra02047f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vertical ordering of block copolymer films by tuning molecular mass

Abstract: We demonstrate that an increase in the molecular mass (chain length N) of a cylinder-forming PS-PMMA block copolymer (BCP), and thus the Flory-Huggins interaction strength cN, allows us to form wellorganized surface patterns having the technologically interesting perpendicular cylinder BCP orientation with respect to the substrate. Tuning the polymer mass also allows for a precise control of the in-plane BCP cylinder pattern wavelength l and gives rise to a local height variation of the BCP film in which the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…14,15 Turning the problem around, the addition of polymers to a binary solvent mixture can greatly alter its miscibility, tending to make the mixture less miscible when the polymer segments are energetically and structurally similar to molecules of only one of the solvent components (but dissimilar to the other). [16][17][18][19] On the other hand, similarity between the polymer units and the solvent molecules of both species induces enhanced miscibility of the system. [16][17][18][19] This situation also occurs, for instance, for solutions of a block copolymer in a homopolymer blend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Turning the problem around, the addition of polymers to a binary solvent mixture can greatly alter its miscibility, tending to make the mixture less miscible when the polymer segments are energetically and structurally similar to molecules of only one of the solvent components (but dissimilar to the other). [16][17][18][19] On the other hand, similarity between the polymer units and the solvent molecules of both species induces enhanced miscibility of the system. [16][17][18][19] This situation also occurs, for instance, for solutions of a block copolymer in a homopolymer blend.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] On the other hand, similarity between the polymer units and the solvent molecules of both species induces enhanced miscibility of the system. [16][17][18][19] This situation also occurs, for instance, for solutions of a block copolymer in a homopolymer blend. 20 Interestingly, the opposite phenomenon, i.e., insolubility of the polymer in each component of binary polymer blends can sometimes induce greater miscibility of the blends.…”
Section: Introductionmentioning
confidence: 99%
“…66 To illuminate this interesting disorder effect from an experimental standpoint, we measured films near the transition region (in both thickness and temperature), but with a horizontal orientation at the top surface. We observe that the first layer of BCP chains coat the substrate and particles, consistent with their chemical affinities.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…We have also recently observed an analogous transition by reducing BCP molecular mass. 66 To illuminate this interesting disorder effect from an experimental standpoint, we measured films near the transition region (in both thickness and temperature), but with a horizontal orientation at the top surface. Using RSANS, we observe a mixed state, which includes a substantial (sometimes dominant) vertical orientation.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The magnetic field has previously been used for directing nanomaterial assembly to create scalable vertically ordered c -BCP nanostructures for organic electronics and transport membrane applications. The alignment of c -BCPs using strong permanent magnets in conjunction with a thermal field demonstrated microstructure control by coupling the magnetic contrast in the system to the intermaterial dividing surface between the BCP microdomains. In addition, Zhang et al , had observed that, in c -BCP PS-PMMA systems, surface and bulk cylindrical microdomains orient vertical at relatively “lower” temperatures, as compared to annealing at “higher” temperatures wherein they observed completely laying down parallel cylinders by the traditional oven annealing method. The temperature at which a transition in the surface pattern morphology is observed depends upon the molecular mass of the BCP, however a base PMMA wetting layer nevertheless existed in all cases.…”
mentioning
confidence: 99%